The Effect Of Shop Atmosphere, Product Diversity, Taste Of Taste, Price And Lifestyle On Consumer Purchase Decision (Studies in Cafe Happy Ice Cream Sukarame, Bandar Lampung) - Ratna Mulyaningsih; Lestari Wuyanti (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2018)
This study aims to identify and analyze how much influence the atmosphere Stores,Diversity Items, Taste, Price and Lifestyle on consumer purchasing decisions are perceived byconsumers in Cafe Happy Ice Cream Sukarame, Bandar Lampung.Research methods used in this research is the method of observation, interviews, questionnaires, andliterature study using Likert scale and sampling methods used is Nonprobality sampling and purposivesampling of 100 samples. The method of analysis used is multiple linear regression method.The results showed that the purchasing decisions comprising Atmosphere Stores (X 1), ProductDiversity (X 2), Taste (X 3), Price (X 4) and Lifestyle (X 5) together have a positive influence. Where theregression equation Y = 4,099 + 0,078 X1 + 0,331 X2 + 0,230 X3 + -0,678 X4 + 1,461 X5+ 2,850Moreover, the simultaneous test (F test) seen that the atmosphere Stores, Diversity Items, Taste Priceand Lifestyle have a significant influence on consumer purchase decisions with a significance level of0.000. However, based on partial test (ttest), variables that have a significant influence on consumerpurchasing decisions with significant levels such as for Diversity Products 0.003, Price 0.001 andLifestyle 0.000. While that does not affect the Store Atmosphere of 0.052 and taste Cake of 0.053. Ofthe five variables that influence consumer purchase decisions in Cafe Happy Ice Cream Sukarame,Bandar Lampung, the most dominant variable is a variable Lifestyle by ttest results.